THE EFFECTS OF ACTINOMYCIN D ON THE ULTRASTRUCTURE OF THE NUCLEUS OF THE AMPHIBIAN EMBRYONIC CELL - Jones, K. W. (The Rockefeller University Press, 1964)
Observations have been made of ultrastructural modifications induced in the nuclei of differentiating amphibian embryonic cells cultured in the presence of Actinomycin D. Of particular interest are regions within the nucleus (regions otherwise rather empty) containing loose groupings of uniform threads having a diameter of around 200 A. These threads have been observed in continuous lengths up to 0.5 µ, and appear to be composed of subfilaments. It is suggested, after taking account of some recent work on lampbrush chromosomes, that these threads are lengths of uncoiled chromosome in a condition of heterosynthetic inhibition. It is further suggested that active and inactive portions of the genome may be distinguishable by the facility with which they can be induced to undergo this ultrastructural modification.